Rancang Bangun Media Pembelajaran Berbasis Virtual Reality Dengan Pendekatan Metode Scrum - Wijatmiko, Arfiandi; Prihadi Mahardhika, Galang (Universitas Muhammadiyah Magelang, 2022)
Learning media is a media that can be used by teachers to deliver learning materials to students. Learning media can be developed in the form of various activities, one of which is outbound activities. Outbound is a learning method carried out in the form of experiential learning through light game activities to hone intelligence and agility. In the digital world, outbound activities can be done with the help of Virtual Reality (VR) technology. VR is a computer technology that allows users to interact in a virtual world environment. With a few modifications, VR technology can be used to support play and learning activities. This research was conducted to develop a VR-based learning media called Edubound. The development of Edubound is carried out using the Scrum method. Based on the results obtained, the scrum method used in this study proved to be quite responsive and adaptive in handling user needs. On the other hand, the speed of developing Edubound learning media which is the main focus in this research can also be accommodated well by the Scrum method. In general, it can be concluded that the Scrum method can work well in the process of developing Edubound learning media.